DEVELOPMENT OF AN AUTOMATED PORTABLE TYRE INFLATOR REGULATOR - Uguru-Okorie, Daniel C.; Adeoye, Judah T.; Adebimpe, Abiodun M.; Ilesanmi, Oluwaseun A. (FUDMA JOURNAL OF SCIENCES, 2025)
Tyre pressure is a critical factor influencing vehicle safety and performance. Overinflated tyres are prone to blowouts, whereas underinflated tyres can overheat quickly, causing structural damage and shortening their lifespan. To mitigate these risks, there is need to develop an inflation monitoring device that automatically cuts off the air supply once the recommended tyre pressure is achieved. The device integrates an ATmega8A microcontroller, a strain gauge pressure sensor, an LCD, a matrix keypad, a solenoid valve, a pressure relief valve, a polyurethane hose, and quick-connect fittings within a PVC junction box casing. Thirty tests were conducted on each tyre type to evaluate the device’s accuracy and precision. Metrics such as absolute error, percentage error and standard deviation were used. The results showed absolute error, percentage error and standard deviation ranged from 0.01 PSI to 0.157 PSI, 0.013 to 0.522% and 0.255 PSI to 0.364 PSI respectively. Paired t-test at a 95% confidence level were conducted with the p-values for trucks, motorcycles and off-road tyres showing the results are statistically significant but that of passenger car and bicycles were not statistically significant. While the metrics for accuracy and precision varied slightly with various tyre types, the values remained within the ± 2% acceptable limit recommended by the International Organisation for Standardisation in ISO 21759:2006. The findings show that this inflation control device can significantly enhance vehicle safety and reduce the risks associated with overinflating and underinflating.